A study to assess the knowledge regarding practices of menstrual hygiene and RTI among high and higher secondary school girls: an educational interventional study - Neelkanth, Namita; Singh, Daneshwar; Bhatia, Padma (International Journal Of Community Medicine And Public Health, 2017)
Background: Menstruation still a taboo subject to whisper and so, more difficult to discuss the hygiene, practices, perception and myth associated with it. The very ancient socio -cultural restrictions still play a major role in plenty of reproductive tract infections left undiagnosed. Thus resulting in the potential loss of economy in terms of GDP, medical costs, and status of health. The objectives of the study were to assess the awareness, source of information and problems regarding menstrual hygiene at pre-questionnaire stage and to compare the assessment of awareness at post questionnaire stage after educational intervention provided among the study group; to find out the mean age of menarche among the study group; to find out the knowledge regarding symptoms of reproductive tract infections among the study group; to inculcate safe hygienic practices during menstruation so as to percolate the same during reproductive episodes e.g. termination of pregnancy or uterine bleeding etc. Methods: Convenient sampling with Semi-structured questionnaire method. A girls’ government school chosen for the study with 197 girls including class standard 9th, 10th, 11th and 12th. After the session of pre questionnaire, all girls were included in the study who were present on the day. Results: On statistical analysis, mean age of menarche among girls is 13.5 years. Data regarding awareness level found statistically significant after the completion of study. Conclusions: Satisfactory improvement in hygiene level found post intervention. It could be implied on massive level in all the schools in country. In conformity with, Indian government also came up with the programme of provision of free sanitary pads in government schools.